2000
DOI: 10.1210/en.141.2.598
|View full text |Cite
|
Sign up to set email alerts
|

Iodide Excess Induces Apoptosis in Thyroid Cells through a p53-Independent Mechanism Involving Oxidative Stress

Abstract: Thyroid toxicity of iodide excess has been demonstrated in animals fed with an iodide-rich diet; in vitro iodide is cytotoxic, inhibits cell growth, and induces morphological changes in thyroid cells of some species. In this study, we investigated the effect of iodide excess in an immortalized thyroid cell line (TAD-2) in primary cultures of human thyroid cells and in cells of nonthyroid origin. Iodide displayed a dose-dependent cytotoxicity in both TAD-2 and primary thyroid cells, although at different concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 0 publications
8
108
2
4
Order By: Relevance
“…However, the exact mechanism by which chronic high iodine intake induces hypothyroidism remains unclear. Vitale et al (30) and our previous experimental studies revealed that high iodine intake damages endogenous thyroid peroxidase and induces apoptosis in these cells through a mechanism that involves the generation of free radicals (30)(31)(32), but whether the iodine-induced apoptosis contributes to chronic iodine-induced hypothyroidism is unknown. It has been reported that iodine-induced hypothyroidism usually resolves quickly after iodine withdrawal, but if the administration of iodide continues, overt or subclinical hypothyroidism will persist (33).…”
Section: Discussionmentioning
confidence: 96%
“…However, the exact mechanism by which chronic high iodine intake induces hypothyroidism remains unclear. Vitale et al (30) and our previous experimental studies revealed that high iodine intake damages endogenous thyroid peroxidase and induces apoptosis in these cells through a mechanism that involves the generation of free radicals (30)(31)(32), but whether the iodine-induced apoptosis contributes to chronic iodine-induced hypothyroidism is unknown. It has been reported that iodine-induced hypothyroidism usually resolves quickly after iodine withdrawal, but if the administration of iodide continues, overt or subclinical hypothyroidism will persist (33).…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that iodide (I K ) exerts antiproliferative and apoptotic effects in thyrocytes and that the ratelimiting step for this effect is the conversion of I K to a more reactive iodine species such as molecular iodine (I 2 ) catalyzed by thyroperoxidase (TPO). Indeed, Vitale et al (2000) showed that an excess of potassium iodide (KI) induces apoptosis in cultured thyroid cells, but if TPO activity is blocked with propylthiouracil, the apoptotic effect of KI is eliminated. Moreover, using lung cancer cells (without natural iodine uptake) transfected with the iodide/sodium symporter (NIS) or NIS/TPO, Zhang et al (2003) observed that only in NIS/TPO-transfected cells did excess KI induce apoptosis, indicating that I K from KI needs to be oxidized to have a cytotoxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The overactivation of PARP1 depletes cellular reserves of NAD C and ATP, leading to necrotic cell death via energy failure; it also has been reported that cleavage of PARP1 by caspases prevents excessive activation of the enzyme and that the cells can maintain levels of ATP and NAD C sufficient to induce oligonucleosomal DNA fragmentation (Yu et al 2002, Virag 2005. It is well established that iodine is an antioxidant at low or moderate levels, but it can act as a potent free radical at high concentrations (Pisarev & Gartner 2000, Vitale et al 2000, Smyth 2003, Joanta et al 2006. In the present study, we analyzed the cell cycle arrest and the signaling pathways involved in the apoptotic effect of I 2 and 6-IL in normal and tumoral mammary cell lines.…”
Section: Introductionmentioning
confidence: 99%